Analysis of Vibration Characteristics of Angular Contact Ball Bearings in Aviation Engines Under Changing Conditions - Yanfang Dong; Zibo Yan; Jianyong Sun; Wei Yu; Hai Zhang; Wenbo Zhou; Jihao Jin (Aerospace)
This paper addresses the vibration characteristics of angular contact ball bearings in aircraft engines under variable load conditions. Based on multibody dynamics theory, a dynamic model of the bearing was established. Vibration data under actual operating conditions were obtained using an experimental test platform. This study systematically investigated the influence of rotational speed, axial load, and radial load on the vibration acceleration level of the bearing outer ring. Through a comparison of simulation and experimental data (with an error rate below 10%), the reliability of the model was validated. The results indicate that the bearing vibration acceleration level exhibits a nonlinear increasing relationship with rotational speed. An increase in radial load significantly amplifies the amplitude of acceleration-level fluctuations, while appropriately increasing axial load can reduce bearing vibration intensity. Under variable load coupling conditions, the dynamic interaction between axial and radial forces results in complex nonlinear vibration responses, with a 2 s acceleration time achieving the optimal balance between vibration suppression and efficiency (steady-state average of 70.4 dB). Additionally, the morphological characteristics of the cage center-of-gravity trajectory (such as trajectory disorder and poor smoothness) are closely related to vibration characteristics, revealing the critical role of dynamic load changes in bearing stability. The research results provide a theoretical basis for optimizing the operating conditions, vibration control, and reliability design of aircraft engine bearings.